2011
DOI: 10.1002/art.33314
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal‐associated invariant T cells promote inflammation and exacerbate disease in murine models of arthritis

Abstract: Conclusion. These results indicate that MAIT cells exacerbate arthritis by enhancing the inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
91
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(97 citation statements)
references
References 45 publications
5
91
0
Order By: Relevance
“…The pro‐inflammatory cytokine IL‐17 is associated with SLE and correlated with disease activity,36, 37 whereas IL‐17‐producing T helper type 17 (Th17) cells are involved in driving local inflammation at sites of disease 38, 39. MAIT cells are potent producers of IL‐17 and due to their similar cytometric profile may in fact have constituted many of the ‘Th17’ populations measured in these studies 40. Local cytokine production by MAIT cells within tissues could contribute to lowering the quantitative threshold of immune signalling, a process believed to interact with genetic predispositions to contribute to the initial pathogenic processes in SLE 35.…”
Section: Observations From Specific Diseasesmentioning
confidence: 83%
See 3 more Smart Citations
“…The pro‐inflammatory cytokine IL‐17 is associated with SLE and correlated with disease activity,36, 37 whereas IL‐17‐producing T helper type 17 (Th17) cells are involved in driving local inflammation at sites of disease 38, 39. MAIT cells are potent producers of IL‐17 and due to their similar cytometric profile may in fact have constituted many of the ‘Th17’ populations measured in these studies 40. Local cytokine production by MAIT cells within tissues could contribute to lowering the quantitative threshold of immune signalling, a process believed to interact with genetic predispositions to contribute to the initial pathogenic processes in SLE 35.…”
Section: Observations From Specific Diseasesmentioning
confidence: 83%
“…Chiba et al 40. found that MR1 −/− mice, which lack MAIT cells, had reduced severity of CIA and of collagen antibody‐induced arthritis, whereas CIA was recapitulated by reconstitution with adoptively transferred MAIT cells.…”
Section: Observations From Specific Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, MAIT cells have been recently implicated to serve as regulatory and/or effector cells in patients with multiple sclerosis and murine model of arthritis (25,26). However, MAIT cell levels and functions have not previously been investigated in rheumatic diseases.…”
mentioning
confidence: 99%